2021
DOI: 10.1007/s13197-021-04973-1
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic fermented oat dairy beverage: viability of Lactobacillus casei, fatty acid profile, phenolic compound content and acceptability

Abstract: The combination of oats such as water-soluble oat extract (SOE) and probiotic microorganisms can add nutritional value to the food and benefits to the consumer's health. The SOE contains soluble fiber, whose major soluble fraction is composed of b-glucan contains soluble antioxidants such as ferulic acid, avenanthramides and other phenolic acids. The purpose of this study was to develop a fermented dairy beverage containing SOE, evaluating the viability of the probiotic culture, the fatty acid profile, phenoli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Depending on the aim of the studies, either bacteria, fungi, or yeasts have been used to increase the contents in total phenolics, flavonoids, gamma-aminobutyric acid (GABA), β-glucan, and dephytinization. To ensure that enough cells are ingested by the host for viability in the gastrointestinal tract, a minimum of 6 Log colony forming units per milliliter (CFU mL −1 ) needs to be present in food for it to be considered a probiotic [ 32 ].…”
Section: Methods Employed To Produce Fermented Oatsmentioning
confidence: 99%
“…Depending on the aim of the studies, either bacteria, fungi, or yeasts have been used to increase the contents in total phenolics, flavonoids, gamma-aminobutyric acid (GABA), β-glucan, and dephytinization. To ensure that enough cells are ingested by the host for viability in the gastrointestinal tract, a minimum of 6 Log colony forming units per milliliter (CFU mL −1 ) needs to be present in food for it to be considered a probiotic [ 32 ].…”
Section: Methods Employed To Produce Fermented Oatsmentioning
confidence: 99%
“…Vera Maria Klajn et al developed a fermented soluble oat extract (SOE) beverage using Lactobacillus casei ( L. casei ). It is concluded that the production of novel probiotic fermented dairy beverages can be fermented with the combination of SOE and the probiotic L. casei , which has been proven to be beneficial for consumers [ 20 ]. Furthermore, β-glucan, the primary dietary fiber component in oat, has been shown to be a probiotic, promoting the growth of beneficial microbiota [ 3 , 21 , 22 ].…”
Section: Strainsmentioning
confidence: 99%
“…Oats ( Avena sativa ) is the major source of beta‐glucan, which is the functional component of cereal fibers (Güler‐Akin et al, 2016). Some functional oat‐beverage are oat extract with L. casei (Klajn et al, 2021), oats and soybean (Moretto et al, 2021), and oats and inulin (Güler‐Akin et al, 2016). Further, inulin, a prebiotic fiber, is a functional polysaccharide widely used as a substitute for sugar and fat, which has a low calorific value and can prevent the sedimentation of beverages (Martono et al, 2019).…”
Section: Introductionmentioning
confidence: 99%